Design, Modeling, and Analysis of IEEE Std 80 Earth Grid Design Refinement Methods Using ETAP - Vuyani Michael Nicholas Dladla; Agha Francis Nnachi; Rembuluwani Philip Tshubwana (Applied Sciences, 2023)
The design of a compliant, safe, and reliable substation earth grid is not a straightforward process; in most cases, it requires some additional measures to be taken due to various constraints that differ from environment to environment, such as soil resistivity, a high fault level, a limited surface area, construction budget, etc. The IEEE Std 80-2013 proposes various refinement methods that can be applied to address different situations. For this study, the current limiting method, current diversion method, and touch and step voltage increment method were applied using the Electrical Transient Analysis Program (ETAP). A power system was designed, where a fault current generated by the supply transformers and back-fed by the power system’s motors was exported to the earth grid. Using this fault current, various simulations were conducted to assess the performance of the earth grid. The analysis results show that the application of the current limiting method using neutral earthing resistors has a great impact on the design of the earth grid as this method significantly reduces the fault current injected into the earth grid. Furthermore, by applying the current diversion method, the amount of fault current injected into the earth grid is reduced by a fair amount, which improves the performance of the earth grid. Lastly, increasing the tolerable limits of touch and step voltages by reducing the fault clearance times significantly improves the compliance of the earth grid as the clearance time is reduced. From this study, it is therefore concluded that, by implementing the refinement methods depending on the design requirements and feasibility of the application, one can improve the compliance state of an earth grid.